(untitled) (Revista Brasileira Multidisciplinar, 2011)
This paper discusses the Brazilian agrarian reform as a tool for regional development. It discusses the current rural settlement policy and its importance in the interaction processes with local dynamics and regional development, investigating the changes that these projects may cause in the municipalities where they are developed.The central point of discussion of this work is Polanyi’s arguments about the factors of production, land, labor and capital, and Amartya Sen’s arguments on freedom as a development factor. The discussion calls for land reform as a way to provide opportunities and a condition of agents to its beneficiaries. Even recognizing the limits faced by this policy, the issue highlighted here refers to the need for land reform not to be limited to the granting of assets to its beneficiaries, but may actually increase their freedoms. We argue that access to land, to means of production, ensures the employee control over his workforce, putting him in a situation of protagonist that can contribute to development, since the economic function is just one among many vital functions in earth. Thus, access to land, the debate about land reform should not be seen simply as an economic instrument, but as a condition of life and social reproduction, the element relating to the organization of social, economic and political relationships.